Lessons learnt from the medical and psychosocial evaluation of childhood acute lymphoblastic leukemia (ALL) survivors enrolled in EORTC Children Leukemia Group Trials between 1971 and 1998 and future perspectives for long-term outcome research. (May 2018) - Piette, Caroline; de Rojas, Teresa; Suciu, Stefan; Kicinski, Michal; Bertrand, Yves; de Schaetzen, Gaetan; Gilotay, Caroline; Meulemans, Bart; Rossi, Séraphine; Röhrlich, Pierre; Benoit, Yves
Highlights: The survival of acute lymphoblastic leukemia (ALL) dramatically increased over the last 40 years. Long-term survivors face late morbidity, late mortality and psychosocial troubles. The EORTC Children's Leukemia Group assessed the long-term outcome of 2621 childhood ALL survivors in the framework of the project 58LAE. This project has raised several challenges when translated into the "real-life" setting. New ways of addressing survivorship studies are needed. Abstract: Acute lymphoblastic leukemia (ALL) is the most common childhood cancer. With dramatic improvements in survival observed since the 70's, it progressively became evident that the long-term survivors faced late morbidity, late mortality and psychosocial troubles. In 2010, the EORTC developed the retrospective 58LAE study in order to evaluate the long-term outcome of the 2621 eligible childhood ALL survivors enrolled between 1971 and 1998. The first sub-project project showed that ETV6-RUNX1 positive patients had better long-term outcome and had specific sensitivities to treatments. The second sub-project showed that omission of cranial radiotherapy did not increase the risk of relapse and was associated with a higher incidence of second neoplasms and late toxicities in medium and high-risk patients, without central nervous system (CNS) involvement. The third sub-project identified hematopoietic stem cell transplantation, cranial radiotherapy and having a relapse as risk factors for worse socio-economic outcome. Finally, the fertility status of the survivors was also evaluated. The 58LAE project has raised several challenges when translated into the "real-life" setting, which include the difficulties of following childhood cancer survivors throughout their transition to adult life; the statistical analysis of a cohort of patients treated in multiple clinical trials and along different years; the need for combining different approaches to gather sufficient quality patient data; and the challenge of overcoming the healthcare administrative and regulatory obstacles. New ways of addressing survivorship studies are needed to address these challenges.